Three‐dimensional velocity structure of the outer fore arc of the Colombia‐Ecuador subduction zone and implications for the 1958 megathrust earthquake rupture zone. Issue 2 (7th February 2014) - García Cano, Lina Constanza; Galve, Audrey; Charvis, Philippe; Marcaillou, Boris
Abstract In 2005, an onshore, offshore 3‐D refraction and wide‐angle reflection seismic experiment was conducted along the convergent margin at the border between Colombia and Ecuador, over the rupture zone of the 1958, Mw 7.6 subduction earthquake. A well‐defined Vp velocity model of the plate boundary and upper and lower plates was constructed, down to 25 km depth, using first arrival traveltimes inversion. The model reveals a several kilometers thick, low‐velocity zone in the upper plate, located immediately above the interplate contact. This low‐velocity zone might be related to alteration and fracturing of the mafic and ultramafic rocks, which composed the upper plate in this area by fluids released by the lower plate with possible contributions from sediment underplating. Near the toe of the margin, the model shows a low‐velocity gradient in the outer wedge, which is interpreted as highly faulted and fractured rocks. This low‐velocity/low‐gradient region appears to limit the oceanward extension of the rupture zones of the 1958 and 1979 earthquakes, possibly because coseismic deformation and uplift of the outer margin wedge dissipates most of the seismic energy.